Renal functional improvement after pediatric pyeloplasty in kidneys with split renal function less than 20%: a single institute experience - Elsayed Salih; Ibrahim Abdelmaksoud; Mohamed Elfeky; Gamal Selmy; Hussein Galal; Mohsen Zekry (SpringerOpen, 2021)
Abstract Background Pediatric pyeloplasty in ureteropelvic junction obstruction (UPJO) is indicated in renal impaired drainage or renal function deterioration. The improvement of renal function after pediatric pyeloplasty is still controversial in poorly functioning kidneys. Past studies on poorly functioning kidneys had a variable SRF specification, and these studies often had a limited number of patients so that they did not achieve statistical significance. The study aims to detect the renal functional improvement after pediatric Anderson-Hynes pyeloplasty (AHP) with split renal function (SRF) less than 20% (poor renal function). Results A retrospective study included 46 pediatric patients with unilateral UPJO who underwent open AHP with SRF < 20% on a renal isotope scan from August 2012 to October 2018. Success was defined based on either improvement in symptoms, improvement in drainage on postoperative renography, and/or improvement or stability in SRF on the renal scan done 6 months postoperatively and yearly thereafter. Deterioration of SRF by more than 5% was deemed to be deterioration. An increase in SRF of more than 5% was deemed to be an improvement. A total of 46 patients with a mean age of 32 months with poor renal function on isotope renogram (SRF < 20%) were included. All patients had an obstructive pattern on the preoperative radionuclide scans. The median preoperative SRF was 9.26%. The mean (range) follow-up was 30 months. The success rate was 91.3%. Three patients underwent redo pyeloplasty, whereas a secondary nephrectomy was necessary for one. The remaining (42) patients showed stability or improvement of SRF with no further symptoms. Renal scintigraphy at 6 and 12 months after surgery revealed significantly increased SRF compared to preoperative one. Conclusion Poorly functioning renal unit with SRF < 20% can show functional improvement and recoverability after pediatric pyeloplasty.